Studi In-Vivo Antifertilitas Stigmasterol Daun Beluntas (Pluchea indica L.): Pengamatan Konsentrasi dan Motilitas Spermatozoa - Fatah, M. Arya; Susetyarini, Eko; Waluyo, Lud; Nurrohman, Endrik (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Low public participation in contraception is one of the factors contributing high population density in Indonesia. Indonesia is known as a paradise for medicinal plants, there are many herbs that have the potential to be developed as contraceptives, one of which is the beluntas plant. This study aims to determine the effect of administering various doses of beluntas leaf stigmasterol on the concentration and motility of spermatozoa. The research was conducted at the Biomedical Laboratory, Muhammadiyah University of Malang, Campus 2 for 45 days. This type of research uses true experimental research with a RAL experimental design, consisting of four treatments and six replications. The doses for each treatment are P1 (0.25mg/gbb), P2 (0.5mg/gbb), P3 (0.75mg/gbb) and control (water). The results showed that administering the entire dose of stigmasterol had a significant effect on the concentration and motility of spermatozoa (P<0.05). Spermatozoa concentration P1 (11.83 ± 1.835), P2 (8.17 ± 1.472), P3 (6.33 ± 1.033), control (21.83 ± 3.312). Spermatozoa motility P1 (32.23 ± 25.406), P2 (19.85 ± 7.173), P3 (17.16 ± 2.801), control 975.23 ± 14.417). Stigmasterol from beluntas leaves has potential as a natural antifertility agent in men.